1977
DOI: 10.4315/0362-028x-40.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Commercially Produced Dried Dog Food: Possible Relationship to a Human Infection Caused by Salmonella enteritidis Serotype Havana

Abstract: Identification of Salmonella enteritidis serotype Havana, isolated from a 2½-month old female, engendered efforts to trace the source of infection. The inquiry led to examination of commercially prepared dehydrated dog foods. Twenty-five samples, representing four different manufacturers plus two retail store brands, were examined. Each of 11 samples, produced by one manufacturer, contained one or more Salmonella serotypes. Eight of them contained S. enteritidis serotype Havana. Isolates of serotype Havana fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Different studies have recorded that serovars found more frequently in dog faeces are similar to those found in humans [10,12,22,32,36,37]. In the present study, three serotypes were isolated, monophasic Salmonella Typhimurium (16.7%), S. Havana (50%) and S. Mikawasima (33.3%), which have also been implicated in human salmonellosis [38][39][40]. All serotypes have been reported previously in dogs and humans [1,16,18,[39][40][41][42][43][44][45], and they have also been reported to be present in raw food [1,39].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Different studies have recorded that serovars found more frequently in dog faeces are similar to those found in humans [10,12,22,32,36,37]. In the present study, three serotypes were isolated, monophasic Salmonella Typhimurium (16.7%), S. Havana (50%) and S. Mikawasima (33.3%), which have also been implicated in human salmonellosis [38][39][40]. All serotypes have been reported previously in dogs and humans [1,16,18,[39][40][41][42][43][44][45], and they have also been reported to be present in raw food [1,39].…”
Section: Discussionsupporting
confidence: 59%
“…This serotype has been isolated previously from poultry products [46]. Pace et al [38] determined a possible human infection caused by S. Havana from dog food contamination. S. Mikawasima has also been found in both wild boar from cattle-free and cattle-grazed areas in Spain [47], and in our study, S. Mikawasima was isolated from one hunting dog in contact with these species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that pet food may be heavily contaminated with Salmonella species and may lead to the contamination of human food when dogs are fed in the kitchen (Christopher and others 1974, Pace and others 1977). However, these reports are old and the data may not apply to modern commercial pet foods.…”
Section: Discussionmentioning
confidence: 99%